Artificial Intelligence Adoption on Investment Platform for Robo Advisory Users in Indonesia - Fahruri, Arief; Rusmanto, Toto; Warganegara, Dezie Leonarda; Tjhin, Viany Utami (Society of Visual Informatics, 2025)
Robo-advisors provide an alternative financial solution tailored for regular clients. Beyond the acceptability of technology, financial factors significantly influence the adoption of robo-advisors. While existing studies extensively discuss the stages involved in the intention to utilize robo-advisors, only a few offer insights into financial capabilities. The purpose of this study is to investigate the extent to which Indonesian investors embrace robo-advisors by incorporating financial variables such as financial goals and financial literacy into the technology adoption in Robo Advisor. Additionally, the study explores the relationship between application costs and data privacy on the adoption of robo-advisor technology. This research employs a quantitative approach using purposive sampling techniques. Data were collected through a survey of 431 robo-advisor users and analyzed using SmartPLS. The findings reveal a significant and positive correlation between financial goals, perceived technology usefulness, and application costs in the adoption of robo-advisors in Indonesia. These results contribute to the development of investment decision theory using technology-based approaches, specifically robo-advisors. Furthermore, companies in the financial sector, particularly in wealth management or investment management, can benefit from incorporating financial goal features, enhancing technological performance, and setting competitive fees to increase adoption rates. Future research should further explore robo-advisor adoption, focusing on additional financial variables and financial behaviors that drive technology adoption as an investment decision. These findings highlight the importance of considering both financial and technological factors in promoting the use of robo-advisors among investors especially in Indonesia.